Model-independent measurement of the excited fraction in a magneto-optical trap - Shah, M. H.; Camp, H. A.; Trachy, M. L.; Veshapidze, G.; Gearba, M. A.; DePaola, B. D. (My University, 2007)
In many experiments involving a magneto-optical trap (MOT) it is of great importance to know the fraction of atoms placed in an excited state due to the trapping process. Generally speaking, researchers have had to use overly simplistic and untested models to estimate this fraction. In this work, the excited fractions of 87Rb atoms in a MOT are directly measured using a charge transfer technique, for a range of MOT parameters. Simple models are then fit to the measured fractions. Using the results of this work, the excited fraction of 87Rb atoms trapped in a MOT can be accurately estimated with knowledge of only the trapping laser intensity and detuning. The results are, at most, only weakly dependent on other MOT parameters.